Limit analysis of shallow foundations and a review of traditional and non-linear constitutive models (2011)
For centuries the construction of good foundations has been of main interest in all civilizations given the importance it has on behavior and performance of structures. However, main developments in soil mechanics theory have taken place in the last centuries. The main goal of this work is to offer a detailed explanation of the theoretical formulation of limit analysis and describe the basic theories in which bearing capacity problems are solved. Plasticity theory is introduced and some constitutive models are described in order to present an alternative approach for solving soil mechanics problems.